2014
DOI: 10.1172/jci78016
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trial demonstrates exercise following bariatric surgery improves insulin sensitivity

Abstract: nondiabetic patients following RYGB surgery are typically quite modest compared with the presurgery condition (3). Moreover, there appear to be 2 discrete periods of improvement. The first is immediately after surgery, at which time hepatic, but not peripheral, S I improves in response to acute energy restriction (4-6), while greater, protracted weight loss appears to be more strongly associated with improved peripheral S I (7,8). Even with significant weight loss 1 year following RYBG surgery, peripheral S I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
199
0
22

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(246 citation statements)
references
References 53 publications
16
199
0
22
Order By: Relevance
“…These findings are consistent with data highlighting that moderate intensity aerobic exercise increases insulin sensitivity and glucose effectiveness (i.e. the ability of glucose to facilitate glucose disposal) [75], along with increased VO 2 max and mitochondrial adaptation for fat oxidation during bariatric-induced weight loss [76]. Supervised endurance exercise or educational based programs with resistance exercise can also facilitate greater weight loss, improved muscle strength and increased fitness capacity [7577], suggesting overall that exercise is an effective therapy to improve metabolic health in surgical patients.…”
Section: Exercise As a Pre-surgical Therapy To Reset Metabolic Responsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with data highlighting that moderate intensity aerobic exercise increases insulin sensitivity and glucose effectiveness (i.e. the ability of glucose to facilitate glucose disposal) [75], along with increased VO 2 max and mitochondrial adaptation for fat oxidation during bariatric-induced weight loss [76]. Supervised endurance exercise or educational based programs with resistance exercise can also facilitate greater weight loss, improved muscle strength and increased fitness capacity [7577], suggesting overall that exercise is an effective therapy to improve metabolic health in surgical patients.…”
Section: Exercise As a Pre-surgical Therapy To Reset Metabolic Responsupporting
confidence: 92%
“…the ability of glucose to facilitate glucose disposal) [75], along with increased VO 2 max and mitochondrial adaptation for fat oxidation during bariatric-induced weight loss [76]. Supervised endurance exercise or educational based programs with resistance exercise can also facilitate greater weight loss, improved muscle strength and increased fitness capacity [7577], suggesting overall that exercise is an effective therapy to improve metabolic health in surgical patients. However, despite higher exercise volumes in the general population appearing to relate to improved glucose regulation [13, 7879] and cardiometabolic health [80], there is a limitation in the existing body of work on the effects of exercise “dose” on cardiometabolic health maintenance over time as well as on the effectiveness of exercise for the prevention of weight regain.…”
Section: Exercise As a Pre-surgical Therapy To Reset Metabolic Responmentioning
confidence: 99%
“…Increases in skeletal muscle mitochondrial biogenesis, mitochondria content and function have been reported to explain improvements in both insulin sensitivity (Coen et al, 2015a) and increased capacity for fatty acid oxidation (Jong-Yeon et al, 2002). Calorie restriction-induced weight loss also improves insulin sensitivity (Coen et al, 2015b), but in contrast to exercise, does not seem to enhance the capacity of skeletal muscle for fatty acid oxidation (Toledo and Goodpaster, 2013). Remarkably, these lack of improvements in fatty acid oxidation of skeletal muscle mitochondria correspond to the lack of response to weight loss (Coen et al, 2015a), although some studies have shown that calorie restriction increases mitochondrial content (Civitarese et al, 2007) and function (Vijgen et al, 2013).…”
Section: Effects Of Exercise Training and Calorie Restriction-inducedmentioning
confidence: 99%
“…101 As skeletal muscle is the body's largest glucose buffering system, a conserved large muscle mass promotes insulin sensitivity and protects against the metabolic syndrome. [102][103][104] Moreover, FFM, but not fat mass or BMI, is positively associated with self-determined meal size and daily energy intake in humans. 105,106 Thus, a rapid weight loss mainly at the expense of FFM entails the subse quent loss of protective muscle strength and its metabo lic bene fits on the regulation of energy homeo stasis.…”
Section: Weight-loss-dependent Effectsmentioning
confidence: 99%